1991
DOI: 10.1063/1.349300
|View full text |Cite
|
Sign up to set email alerts
|

Insitu observation of the strain of Co and Ni deposited on Pd (111) by reflection high energy electron diffraction

Abstract: Co/Pd(111) and Ni/Pd(111) bilayer films were grown epitaxially on single crystal MgO (111) substrates by ultrahigh vacuum deposition. In situ observation of the strain of Co and Ni deposited on Pd (111) plane was performed by reflection high energy electron diffraction (RHEED) during fabrication. From RHEED patterns it was confirmed that the lattice constant of a Co film of 2 Å in thickness deposited on Pd was about 3.7 Å, which was different from that of Pd (3.89 Å). The strain (εCo) of the Co layer was rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Actually previous works have reported that Pd thin film preferred (111)-orientation when grown on mica [40,41]. The matching between Ni(111) and Pd(111) has also been suggested in Pd/Ni(111) and Ni/ Pd(111) systems [42,43]. Combining the information from previous studies, the (111)-texture of Pd/Ni/Pd/mica observed in our measurement is reasonable.…”
Section: Experimental Methodssupporting
confidence: 85%
“…Actually previous works have reported that Pd thin film preferred (111)-orientation when grown on mica [40,41]. The matching between Ni(111) and Pd(111) has also been suggested in Pd/Ni(111) and Ni/ Pd(111) systems [42,43]. Combining the information from previous studies, the (111)-texture of Pd/Ni/Pd/mica observed in our measurement is reasonable.…”
Section: Experimental Methodssupporting
confidence: 85%
“…The lattice strains of the Co films have been observed by means of EXAFS, XPD, Xray diffraction and RHEED experiments. [11][12][13][14][15] However, it was noticed that the PMA of Co/Pd(111) cannot be explained only from the viewpoint of the magnetoelastic anisotropy. 15) On the other hand, it is considered that the anisotropy of the orbital moment and the spin-orbit interaction in the electronic structure cause the PMA.…”
Section: Introductionmentioning
confidence: 99%
“…Table I shows the average strain ( E ) in 1st deposited layer of Pd on Ni or Ni on Pd derived from the simulated results. Yamazaki et al [7] reported that they observed the strain in Ni layer on Pd (111) by using RHEED during evapolation and there was no strain at interface. This corresponds well to the simulated result.…”
Section: Resultsmentioning
confidence: 97%